How important is the credit channel? An empirical study of the US banking crisis - Chunping Liu; Patrick Minford (Cardiff University, Cardiff Business School, 2012)
We examine whether by adding a credit channel to the standard New Keynesian model we can account better for the behaviour of US macroeconomic data up to and including the banking crisis. We use the method of indirect inference which evaluates statistically how far a model is simulated behaviour mimics the behaviour of the data. We find that the model with credit dominates the standard model by a substantial margin. The credit channel is the main contributor to the variation in the output gap during the crisis.
Keywords: C12; C52; E12; G01; G1; 330; financial frictions; credit channel; bank crisis; indirect inference